Equity of African American Men in Headache in the United States: A Perspective From African American Headache Medicine Specialists (Part 1). Issue 10 (3rd November 2020) - Charleston, Larry; Spears, Roderick C.; Flippen, Charles
Abstract : Migraine and severe headache affect approximately 1 in 6 U.S. adults and migraine is one of the most disabling disorders worldwide. Approximately 903, 000 to 1.5 million African American (AA) men are affected by migraine in the United States. Racial disparities in headache medicine exist. In addition, there are limited headache studies that attest to the inclusion of or have robust data on AA men in headache medicine in the United States. Racial concordance between provider and patient may ameliorate some aspects of care disparities. Moreover, it has been demonstrated that diversity and inclusion particularly in leadership of organizations has consistently produced positive change, increased innovation, and long‐term success. Most national headache organizations strive to improve the care and lives of people living with headache disorders yet only ~0.5% of their physician members are AA men. Herein, we provide an observation of equity issues from the perspective of AA men in the headache medicine subspecialty. Part 1 of this manuscript explores inherent and potential challenges of the equity of AA men in headache medicine including headache disparities, mistrust, understudied/lack of representation in research, cultural differences, implicit/explicit bias, and the diversity tax. Part 2 of this work offers possible solutions to achieve equity for AA men in headache including: (1) addressing head and facial pain disparities and mistrust in AA men; (2) professionalism and inclusion; (3) organizational/departmental leadership buy‐in for racial diversity; (4) implicit/explicit and other bias training; (5) diversity panels with open discussion; (6) addressing diversity tax; (7) senior mentorship; (8) increased opportunities for noteworthy and important roles; (9) forming and building alliances and partnerships; (10) diversity leadership training programs; (11) headache awareness, education, and literacy with focus to underrepresented in medicine trainees and institutions; and (12) focused and supported the recruitment of AA men into headache medicine. More work is needed for equity of AA men in headache medicine.